The physical environment as a three-dimensional textbook for environmental education in Malaysian primary schools / Kong Seng Yeap - Kong, Seng Yeap (2014)

(untitled)
Environmental education (EE) for primary schools in Malaysia is often linked to abstract representation in a featureless classroom. What has often been overlooked is the potential use of physical environment to enrich the EE experience. Instead of focusing on what is taught and how it is taught, equal attention should be given to the physical environment in which EE occurs. With the increased recognition that EE should find a special consideration in educational facilities design, a small, growing literature about the subject is emerging. Practitioners and scholars attempt to bond architecture and EE by designing physical environment as a threedimensional (3-D) textbook. Although the notion of a 3-D textbook promises a lot of benefits to the teaching and learning of EE, research on this subject is relatively scarce in the literature. To date, there has been no systematic effort to formulate an effective design model for the 3-D Textbook. This study sets out to explore two knowledge gaps. Firstly, ‘what are the design features for the 3-D textbook?’ Although previous researches illustrate some of the content and benefit of the 3-D textbook, the scholars have not explicitly elaborated on the design features. The answer to the first question would provide a series of design features for further testing and validation. It leads to the second enquiry: ‘Can the 3-D textbook enhance EE outcomes?’ Although some scholars claimed that the 3-D textbook is a useful educational tool, the effectiveness of this architectural intervention has not been evaluated in the literature. iv To achieve these goals, a two-phase, sequential exploratory mixed methods had been employed. The purpose was to develop and test a design model for the 3-D textbook. Phase 1 was a two-week qualitative case study in Green School, Bali. The reason for collecting qualitative data initially was that the design features were not known and that these variables needed to be identified based on a case study. Data was collected through a series of interview and on-site observation. Through content analysis, four design features emerged: ‘Transparency’, ‘In One with Nature’, ‘Creativity & Imagination’ and ‘Active Setting’. From the results of the qualitative study, the author further developed the tentative hypotheses which emerged out of literature review. Subsequently, a quasi experiment involving two groups of standard five students (i.e. comparison & participant) was used to test the hypotheses and generalize the design features. The participant group took part in the design, build and operate of a physical model which evolved from the findings of Phase 1. ANCOVA tests revealed that the 3-D textbook had a significant (p<.05) positive effect on EE outcomes. The participant group demonstrated an improvement in pro-recycling knowledge, attitudes and behaviour as compared to their peers who had not interacted with the 3-D textbook. This study offers significant contribution to both theory and practice related use of architecture in EE. It serves as a catalyst for further research on academic architecture. Keywords: 3-D textbook; Architecture; Environmental education; Children; Sustainability